High-hardness, high-binding-force and low-brittleness ceramic coating on surface of aluminum alloy and preparation method
By using physical vapor deposition and laser nitriding composite technology to form a TiAlN-TiN gradient structure ceramic coating on the surface of the aluminum alloy, the problems of low surface hardness and poor wear resistance of the aluminum alloy are solved, and a hard coating with high hardness, high binding force and low brittleness are achieved, meeting the needs of lightweight precision components in the aerospace field.
Patent Information
- Application Number
- CN202411477896.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
AI Technical Summary
The surface hardness of aluminum alloys is low and wear-resistant, making it difficult to meet the surface hard coating requirements of light metal materials in the aerospace field.
Using physical vapor deposition and laser nitriding composite technology, a TiAlN-TiN gradient structure ceramic coating is formed on the surface of aluminum alloy, and a hard coating with high hardness, high binding force and low brittleness is achieved by pre-plating Ti-Al and Ti gradient transition layers.
It significantly improves the surface hardness and wear resistance of aluminum alloys, reduces the surface roughness, and meets the application needs of lightweight precision components in the aerospace field.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a high-hardness, high-bonding-force and low-brittleness ceramic coating on the surface of an aluminum alloy, belonging to the technical field of hard coatings on the surface of aerospace lightweight metal materials. Background Art
[0002] Aluminum alloys have the advantages of low density, high specific strength, high specific stiffness, good corrosion resistance, and good low-temperature mechanical properties. They are widely used in the aerospace field to prepare satellite pointing mechanisms, space robotic arms, lunar rover wheels and other products. However, due to the low hardness and poor wear resistance of aluminum alloys, related motion mechanisms face serious wear problems during long-term in-orbit service, posing risks to product life and reliability.
[0003] In order to solve the problems of low surface hardness and poor wear resistance of aluminum alloy components, the traditional aluminum alloy surface strengthening technologies mainly include: anodizing, thermal spraying, cold spraying, vapor deposition, laser shock strengthening and other means. Among them, anodizing has problems such as large film brittleness and easy cracking, which is not suitable for surface strengthening of motion mechanism products; thermal spraying wear-resistant coatings have problems such as large surface roughness, large product thermal stress, and poor coating bonding strength, which cannot meet the surface implementation requirements of precision parts; cold spraying is prone to severe plastic deformation, resulting in reduced product precision; physical / chemical vapor deposition hard films have problems such as large hardness difference between the film layer and the substrate, easy to generate internal stress, low bonding strength, and thin coating thickness; laser shock strengthening can improve the surface hardness and crack propagation resistance by implementing fine grain strengthening and residual compressive stress on the surface of the substrate, but the effect of improving hardness and wear resistance is limited.
[0004] Laser nitriding technology is a method for preparing hard coatings with good process feasibility, high stability and environmental protection. It can form hard phases such as FeN and TiN on the surface of steel and titanium alloys through nitriding reaction. The hardened layer is combined with the substrate by metallurgical bonding, which can greatly improve the surface hardness and wear resistance of the substrate. Compared with nitriding methods such as gas nitriding and plasma nitriding, the material does not need to enter a sealed high-temperature nitriding furnace for high-temperature nitriding reaction, and can achieve both good surface hardening effect and good mechanical properties of the substrate. However, due to the restriction of elemental reaction activity, various nitriding technologies including laser nitriding are only suitable for iron-based and titanium-based materials, such as cast iron, carbon steel, alloy steel, stainless steel and titanium alloy, and are difficult to apply to the surface strengthening modification of light alloys such as aluminum alloys. Summary of the invention
[0005] The technical problem solved by the present application is: to overcome the shortcomings of the prior art and provide a method for preparing a high-hardness, high-bonding strength and low-brittleness ceramic coating on the surface of an aluminum alloy. The method of the present invention can form a hardened layer with high hardness, high bonding strength and low brittleness on the surface of the aluminum alloy, which can significantly solve the problems of low surface hardness and poor wear resistance of the aluminum alloy substrate. The coating has a low surface roughness, which expands the application of aluminum alloys in lightweight precision components such as aerospace motion mechanisms.
[0006] The technical solutions provided by this application are as follows:
[0007] The present invention provides a method for preparing a high-hardness, high-bonding-force and low-brittleness ceramic coating on an aluminum alloy surface, comprising the following steps: aluminum alloy substrate pretreatment (cleaning and drying), physical vapor deposition of Ti-Al and Ti transition layers, laser nitridation treatment, and stress relief heat treatment.
[0008] Among them, physical vapor deposition Ti-Al and Ti transition layer:
[0009] Preferably, the physical vapor deposition Ti—Al and Ti transition layer target materials are composed of Ti-20-50wt% Al and pure Ti, respectively.
[0010] Preferably, the physical vapor deposition is DC magnetron sputtering.
[0011] Preferably, the ratio of the deposition time during physical vapor deposition of the Ti—Al transition layer to the deposition time during physical vapor deposition of the Ti transition layer is 1:2 to 2:1.
[0012] Preferably, the physical vapor deposition power is preferably 80W-180W.
[0013] Preferably, the physical vapor deposition is performed under pure argon.
[0014] Preferably, the physical vapor deposition gas pressure is 0.4Pa-1.0Pa.
[0015] Preferably, the physical vapor deposition bias voltage is 30V to 60V.
[0016] Preferably, the physical vapor deposition temperature is room temperature to 100°C.
[0017] Preferably, the physical vapor deposition time is 1 to 8 hours.
[0018] Among them, laser nitriding treatment:
[0019] Preferably, the laser power is 100W to 400W.
[0020] Preferably, the laser spot diameter is 50 μm to 100 μm.
[0021] Preferably, the laser scanning speed is 150 mm / s to 250 mm / s.
[0022] Preferably, the laser overlap rate is 10% to 30%.
[0023] Preferably, the nitrogen / argon flow ratio of the laser nitriding atmosphere is 10:2 to 10:0.
[0024] Preferably, the laser nitriding gas flow rate is 10 L / min to 20 L / min.
[0025] Preferably, the laser nitridation sample heating temperature is room temperature to 100°C.
[0026] Among them, stress relief annealing heat treatment:
[0027] Preferably, the heat treatment working temperature is 50°C to 100°C, and the insulation time is 1h to 8h.
[0028] Preferably, the heat treatment heating method is heating with the furnace, and the cooling method is air cooling after leaving the furnace.
[0029] The present invention adopts a method of physical vapor deposition and laser nitriding to prepare a hard coating with high bonding strength and high flatness on the surface of an aluminum alloy. The main component of the coating is TiN. The specific structure of the coating is as follows: the surface of the aluminum alloy substrate is a TiAlN interface layer, a Ti-TiN mixed layer, and a TiN layer in sequence. The coating thickness is 500nm to 300μm, the surface roughness Ra is better than 3.2μm, the Vickers hardness of the coating is ≥900Hv, and the bonding strength of the coating is ≥60MPa.
[0030] In order to improve the problems of poor bonding, high brittleness and poor precision between the surface strengthening and modified layer of aluminum alloy and the substrate, physical vapor deposition and laser nitriding composite technology are used to prepare high bonding and high hardness coatings on the surface of aluminum alloy. First, the aluminum alloy substrate is pre-treated (cleaned and dried); then, Ti-Al and Ti transition layers are deposited on the surface of the aluminum alloy by physical vapor deposition technology; then, the surface of the material is laser nitrided; finally, the coating is subjected to stress relief annealing heat treatment. This technology solves the problems that the surface of the aluminum alloy material cannot be nitrided and only the pre-plated Ti transition layer can be nitrided but the nitriding layer is brittle by pre-plating Ti-Al and Ti gradient transition layers on the surface of the aluminum alloy, thereby realizing the preparation of high hardness and high bonding hard coatings on the surface of the aluminum alloy material; through laser nitriding process control, on the basis of pre-plating Ti-Al and Ti gradient transition layers, the preparation of aluminum substrate-TiAlN-TiN gradient structure hard coating is realized. The coating has high hardness, bonding and low brittleness, and the surface can still maintain low roughness, meeting the surface strengthening requirements of aluminum alloy precision mechanisms.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention uses physical vapor deposition and laser nitriding composite technology, which solves the problem that single laser nitriding technology is not applicable to the surface process of non-ferrous and titanium substrates such as aluminum alloys, and solves the problem that the single physical vapor deposition hard film layer has low matching and poor bonding with the aluminum substrate. It can form a high-hardness, high-bonding, low-brittle ceramic coating on the surface of the aluminum alloy, significantly improve the surface hardness and wear resistance of the aluminum alloy material, and expand its application range. The coating thickness is 500nm~300μm, the surface Vickers hardness is ≥900Hv, the bonding force is ≥60MPa, the brittleness is not less than level 1, and the surface roughness Ra is better than 3.2μm.
[0033] (2) The present invention realizes the gradient distribution of the coating structure through physical vapor deposition and laser nitriding process control, that is, through the method of "pre-plating Ti-Al, Ti gradient transition layer on the surface" + "laser nitriding", an aluminum substrate-TiAlN-TiN gradient coating structure is constructed. The coating uses TiAlN with excellent toughness as the intermediate layer to play a good role in composition and hardness transition. The coating hardness increases from the substrate to the surface, and the aluminum content decreases from the substrate to the surface. There is a good match between the composition and performance of each layer, so that the coating obtains a good match of high hardness, high bonding strength and low brittleness.
[0034] (3) The present invention adopts vacuum physical vapor deposition combined with laser scanning nitriding treatment, and the coating can obtain good surface roughness and can be directly applied without subsequent mechanical processing, meeting the long life and high reliability manufacturing requirements of aerospace aluminum alloy lightweight precision mechanisms. DETAILED DESCRIPTION
[0035] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments disclosed in the present invention are described in further detail.
[0036] Example 1
[0037] The method for preparing a high-hardness, high-bonding-strength, low-brittleness ceramic coating on the surface of 2A12-T4 aluminum alloy in this embodiment is as follows:
[0038] Step 1: Substrate pretreatment
[0039] The aluminum alloy specimens were ultrasonically cleaned with acetone and anhydrous ethanol in turn, with each solvent ultrasonic cleaning time of 15 min to remove oil stains on the surface of the specimens, and then dried with compressed air.
[0040] Step 2: Physical vapor deposition of Ti-Al and Ti transition layers on the aluminum alloy surface
[0041] Ti-Al and Ti transition layers are prepared successively by physical vapor deposition on the aluminum alloy substrate after pretreatment, preferably DC magnetron sputtering. The specific DC magnetron sputtering process parameters are as follows: Ti-20wt%Al is used as the target material for depositing the Ti-Al transition layer, pure argon is used as the working gas, the working pressure is 0.8Pa, the sputtering power is 160W, the bias voltage is 50V, the deposition temperature is room temperature, and the deposition time is 3h; pure Ti is used as the target material for depositing the Ti transition layer, pure argon is used as the working gas, the working pressure is 0.4Pa, the sputtering power is 150W, the bias voltage is 50V, the deposition temperature is room temperature, and the deposition time is 3h.
[0042] Step 3: Laser nitriding
[0043] Laser nitriding treatment is performed on the aluminum alloy sample with a titanium transition layer deposited on the surface, preferably using a continuous laser for laser nitriding. The specific laser nitriding process parameters are as follows: pure nitrogen is used as the working gas, the nitrogen flow rate is 20L / min, the laser power is 350W, the spot diameter is 100μm, the scanning speed is 170mm / s, the overlap rate is 10%, and the working temperature is room temperature.
[0044] Step 4: Annealing
[0045] The samples after laser nitriding were annealed. The specific annealing process parameters are as follows: annealing in an air furnace, heating from room temperature to 100°C and keeping the temperature for 3 hours, and then taking out of the furnace and air cooling.
[0046] According to the above process, the prepared coating has a thickness of 200 μm, a surface Vickers hardness of 920, a bonding force of 65 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0047] Example 2
[0048] The difference from Example 1 is that Ti-30wt%Al is used as the target material for depositing the Ti-Al transition layer. The laser power used for laser nitriding treatment is 300W, the scanning speed is 220mm / s, nitrogen and argon mixed gas is used as the working gas, the nitrogen flow rate is 18L / min, and the argon flow rate is 3.6L / min.
[0049] According to the above process, the prepared coating has a thickness of 160 μm, a surface Vickers hardness of 950, a bonding force of 62 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0050] Example 3
[0051] The difference from Example 1 is that the substrate is 7055-T6 aluminum alloy, and Ti-45wt%Al is used as the target material for depositing the Ti-Al transition layer. The process parameters are the same as those of Example 1.
[0052] According to the above process, the prepared coating has a thickness of 195 μm, a surface Vickers hardness of 980, a bonding force of 70 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0053] Example 4
[0054] The difference from Example 1 is that the laser nitridation process parameters are as follows: laser power is 350 W, spot diameter is 100 μm, scanning speed is 150 mm / s, overlap rate is 10%, and working temperature is room temperature.
[0055] According to the above process, the prepared coating has a thickness of 215 μm, a surface Vickers hardness of 930, a bonding force of 62 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0056] Example 5
[0057] The difference from Example 1 is that the laser nitridation process parameters are as follows: laser power is 150 W, spot diameter is 50 μm, scanning speed is 150 mm / s, overlap rate is 10%, and working temperature is room temperature.
[0058] According to the above process, the prepared coating has a thickness of 220 μm, a surface Vickers hardness of 925, a bonding force of 63 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0059] Example 6
[0060] The difference from Example 1 is that Ti-30wt%Al is used as the target material for depositing the Ti-Al transition layer.
[0061] According to the above process, the prepared coating has a thickness of 150 μm, a surface Vickers hardness of 930, a bonding force of 66 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0062] Example 7
[0063] The difference from Example 1 is that Ti-50wt%Al is used as the target material for depositing the Ti-Al transition layer.
[0064] According to the above process, the prepared coating has a thickness of 145 μm, a surface Vickers hardness of 910, a bonding force of 68 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0065] Example 8
[0066] The difference from Example 1 is that the deposition time of the Ti—Al transition layer by DC magnetron sputtering is 2 hours; and the deposition time of the Ti transition layer is 4 hours.
[0067] According to the above process, the prepared coating has a thickness of 220 μm, a surface Vickers hardness of 940, a bonding force of 61 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0068] Example 9
[0069] The difference from Example 1 is that the deposition time of the Ti—Al transition layer by DC magnetron sputtering is 4 hours; and the deposition time of the Ti transition layer is 2 hours.
[0070] According to the above process, the prepared coating has a thickness of 170 μm, a surface Vickers hardness of 915, a bonding force of 66 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0071] Comparative Example 1
[0072] The difference from Example 1 is that no physical vapor deposition of Ti—Al transition layer is performed on the surface of the aluminum alloy.
[0073] According to the above process, the prepared coating has a thickness of about 170 μm, a surface Vickers hardness of 975 Hv, a coating bonding strength of 40 MPa, a brittleness level of 3, and a surface roughness Ra of 1.6 μm.
[0074] Comparative Example 2
[0075] The difference from Example 1 is that Ti and Ti—Al transition layers are successively prepared by physical vapor deposition on the pre-treated aluminum alloy substrate.
[0076] According to the above process, the prepared coating has a thickness of about 165 μm, a surface Vickers hardness of 815 Hv, a coating bonding strength of 35 MPa, a brittleness level of 2, and a surface roughness Ra of 1.6 μm.
[0077] Comparative Example 3
[0078] The difference from Example 1 is that Ti-75wt%Al is used as the target material for depositing the Ti-Al transition layer.
[0079] According to the above process, the prepared coating has a thickness of about 175 μm, a surface Vickers hardness of 865 Hv, a coating bonding strength of 45 MPa, a brittleness level of 2, and a surface roughness Ra of 1.6 μm.
[0080] Comparative Example 4
[0081] The difference from Example 1 is that the deposition time of the Ti—Al transition layer by DC magnetron sputtering is 5 hours; and the deposition time of the Ti transition layer is 1 hour.
[0082] According to the above process, the prepared coating has a thickness of 175 μm, a surface Vickers hardness of 840, a bonding force of 67 MPa, a brittleness level of 1, and a surface roughness Ra of 1.6 μm.
[0083] According to Examples 1, 4 and 5, based on the Ti-Al transition layer and Ti transition layer defined in the present application, combined with the laser nitriding treatment power parameter range, under the condition of 100-watt small spot fast scanning, the obtained coating has a good surface roughness, Ra reaches 1.6μm, and the coating can also meet the requirements of thickness ≥175μm, surface Vickers hardness ≥870, bonding force ≥62MPa, and brittleness level 1. According to Examples 1, 6 and 7, with the increase of Al content in the Ti-Al transition layer, the obtained coating bonding force is improved, the bonding force is ≥65MPa, the coating can also meet the requirements of thickness ≥145μm, surface Vickers hardness ≥910, brittleness level 1, and surface roughness Ra is 1.6μm. According to Examples 1, 8 and 9, with the increase of Ti-Al transition layer deposition time, the obtained coating bonding force is improved, the bonding force is ≥61MPa, the coating can also meet the requirements of thickness ≥170μm, surface Vickers hardness ≥890, brittleness level 1, and surface roughness Ra is 1.6μm. According to Example 1, Comparative Examples 1 and 2, the Ti-Al transition layer was not physically vapor deposited on the aluminum alloy surface, and the order of transition layer deposition was changed, that is, Ti and Ti-Al transition layers were deposited in sequence, and the coatings all had problems such as low bonding strength and high brittleness. The highest bonding strength was only 40MPa, and the highest brittleness was only level 2. According to Example 1 and Comparative Example 3, the target material composition of the deposited Ti-Al transition layer exceeded Ti-20~50wt%Al, and the coating had problems such as low bonding strength (only 45MPa) and high brittleness (only level 2). According to Examples 1, 8, 9 and Comparative Example 4, the ratio of the time for depositing the Ti-Al transition layer to the time for the Ti transition layer exceeded 1:2~2:1, and the coating had a problem of low hardness (only 840).
[0084] The contents not described in detail in this application specification belong to the common knowledge of those skilled in the art.
[0085] The present application is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limiting the present application. Those skilled in the art understand that, without departing from the spirit and scope of the present application, a variety of equivalent replacements, modifications or improvements can be made to the technical solution of the present application and its implementation methods, all of which fall within the scope of the present application. The scope of protection of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a high-hardness, high-bonding, low-brittle ceramic coating on an aluminum alloy surface, characterized in that: include: A Ti-Al transition layer and a Ti transition layer are sequentially deposited on the surface of an aluminum alloy substrate by physical vapor deposition to obtain an intermediate; The intermediate is subjected to laser nitridation treatment to obtain a laser nitrided sample.
2. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on the surface of an aluminum alloy according to claim 1, characterized in that: When the Ti-Al transition layer is physically deposited by vapor phase, the target material component is Ti-Al alloy, the Al content in the Ti-Al alloy is 20-50wt%; when the Ti transition layer is physically deposited by vapor phase, the target material component is pure Ti.
3. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on an aluminum alloy surface according to claim 1, characterized in that: The process parameters of the physical vapor deposition are: deposition power of 80W-180W, carried out under pure argon gas, pressure of 0.4Pa-1.0Pa, bias voltage of 30V-60V, temperature of room temperature-100°C, and deposition time of 1-8h.
4. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on the surface of an aluminum alloy according to claim 3, characterized in that: The ratio of the deposition time during physical vapor deposition of the Ti—Al transition layer to the deposition time during physical vapor deposition of the Ti transition layer is 1:2 to 2:
1.
5. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on an aluminum alloy surface according to claim 1, characterized in that: The parameters of the laser nitriding treatment are: laser power 100W-400W, laser spot diameter 50μm-100μm, laser scanning speed 150mm / s-250mm / s.
6. The method for preparing a high-hardness, high-bonding-strength, low-brittleness ceramic coating on the surface of an aluminum alloy according to claim 5, characterized in that: The parameters of the laser nitriding treatment also include: a laser overlap rate of 10% to 30%, a laser nitriding atmosphere nitrogen / argon flow ratio of 10:2 to 10:0, a laser nitriding gas flow of 10L / min to 20L / min, and a laser nitriding sample heating temperature of room temperature to 100°C.
7. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on an aluminum alloy surface according to claim 1, characterized in that: After the intermediate body is subjected to laser nitridation treatment, the laser nitrided sample is subjected to stress relief annealing heat treatment.
8. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on an aluminum alloy surface according to claim 1, characterized in that: The working temperature of the stress relief annealing heat treatment is 50° C. to 100° C., and the insulation time is 1 h to 8 h.
9. The method for preparing a high-hardness, high-bonding, low-brittleness ceramic coating on the surface of an aluminum alloy according to claim 8, characterized in that: The stress relief annealing heat treatment is heated in a furnace and cooled in air after being removed from the furnace.
10. A high-hardness, high-bonding, low-brittleness ceramic coating on the surface of an aluminum alloy, characterized by: The coating is prepared according to the method for preparing a ceramic coating with high hardness, high bonding strength and low brittleness on the surface of an aluminum alloy as described in any one of claims 1-9.